KEKERASAN TERHADAP PEREMPUAN: ANALISIS GENDER DALAM TAOISME ISLAM - Muhammad Husni (VICRATINA, 2016)
Abstract Violence against women occurs in different fields of life. Violence is a product of patriarchal culture which does not only effect social realm, but also religious realm. Religion has been one of the sources of justification for fiolance against women. Through a gender analysis, the roots of violence against women can be found. In this context, Islamic Taoism argues that negative masculine characters of human beings are the very roots of violence against women. Thus, Islamic Taoism proposes that equal relations can be maintained if man and woman could control the negative masculine characters within themselves.